Моделювання етапу «Орієнтація» в петлі OODA під час інформаційної війни - Литвин, Василь; Оборська, Оксана (Видавництво Львівської політехніки, 2014)
Develops a theoretical model of internal processes Orientation stage cycle OODA, which is important in terms of information warfare. Any new information is a potential target for manipulation information warfare attack.
Keywords: інформаційна війна; цикл OODA; етап «Орієнтація»